2019
DOI: 10.1111/sltb.12576
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Suicidal Behavior with Telemedicine in Patients with a Recent Suicide Attempt: Is a 6‐month Intervention Long Enough?

Abstract: Objective To analyze the results of a 6‐month telephone follow‐up program for the prevention of suicidality in adult patients discharged from three general hospitals after a suicide attempt. Results are compared with traditional programs lasting 12 months or more. Methods This is a prospective, multicenter, study with the control group. Patients in the intervention group received five protocolized telephone calls which were added to their usual treatment. Those in the control group only received usual treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Sankar et al (2021) found that the intervention had high retention rates (77%), high scores on the client satisfaction questionnaire, and increased participant global scores on the working alliance inventory, which indicates a strong therapeutic alliance (Sankar et al, 2021). Similarly, Gabilondo et al (2020) found that the intervention was well-accepted and showed improved adherence to outpatient follow-up. However, it is important to note that some studies found worse results in preventing suicidality when programmes do not last 12 months or more.…”
Section: Discussionmentioning
confidence: 84%
“…Sankar et al (2021) found that the intervention had high retention rates (77%), high scores on the client satisfaction questionnaire, and increased participant global scores on the working alliance inventory, which indicates a strong therapeutic alliance (Sankar et al, 2021). Similarly, Gabilondo et al (2020) found that the intervention was well-accepted and showed improved adherence to outpatient follow-up. However, it is important to note that some studies found worse results in preventing suicidality when programmes do not last 12 months or more.…”
Section: Discussionmentioning
confidence: 84%
“…Future studies should focus on the implementation and validation of these tools in real-world clinical settings. It is worth noting that a study on telephone follow-up programs for suicide prevention concluded that longer programs lasting ≥12 months were more effective in preventing suicidality compared with shorter programs [ 76 ], highlighting the importance of longitudinal assessment and intervention for suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis based on the criteria already presented showed that not all the interventions had a control group to compare their effects. A proportion of 4/23 in the Spanish sample [21][22][23][24] and 5/23 in the Japanese sample [25][26][27][28][29] included a control group exempt from treatment, although some had a group that received a different treatment, with a…”
Section: Methodological Quality Analysismentioning
confidence: 99%
“…The analysis based on the criteria already presented showed that not all the interventions had a control group to compare their effects. A proportion of 4/23 in the Spanish sample [21][22][23][24] and 5/23 in the Japanese sample [25][26][27][28][29] included a control group exempt from treatment, although some had a group that received a different treatment, with a proportion of 5/23 in the Spanish sample [30][31][32][33][34] and 3/23 in the Japanese sample [35][36][37]. While, in the Japanese sample, two articles [38,39] included the relatives of the patient, in the Spanish sample we found two articles [24,40].…”
Section: Methodological Quality Analysismentioning
confidence: 99%